Driving Performance Through Innovation: The Roles of Communication and Competence in Public Sector Employees - Jopinus Saragih (UIN Sunan Gunung Djati, 2023)
This study investigates the influence of communication and employee competence on innovation and its implications for employee performance within the Badan Pendapatan Daerah (Regional Revenue Agency) Kabupaten Karawang. Understanding these relationships is critical for enhancing organisational efficiency and effectiveness. The study used a quantitative approach with a survey method to collect data from 100 employees at Badan Pendapatan Daerah Kabupaten Karawang. The analysis included descriptive statistics and path analysis to explore the relationships between communication, competence, innovation, and employee performance. Validity and reliability tests were conducted to ensure the instruments' accuracy. The results revealed significant positive correlations between communication and competence (r = 0.693, p < 0.01). Path analysis indicated that communication (Î² = 0.548) and competence (Î² = 0.381) significantly influence innovation, which in turn has a substantial impact on employee performance (RÂ² = 78.8%). These findings highlight that effective communication and high employee competence are crucial drivers of innovation. Moreover, innovation plays a dominant role in enhancing employee performance, suggesting that fostering an innovative work environment is essential for organisational success. The study concludes that improving communication and competence among employees significantly boosts innovation and subsequently enhances employee performance. The findings underscore the need for targeted training programmes and a supportive work environment to facilitate effective communication and continuous skill development. Future research should consider additional factors such as organisational culture and employee motivation to provide a more comprehensive understanding of performance determinants.